Eksistensi Badan Usaha Milik Desa (BUMDES) dalam Upaya Mewujudkan Negara Hukum Kesejahteraan - Alda Rifada Rizqi (Ajudikasi : Jurnal Ilmu Hukum, 2019)
The Village Government is an administrative entity that currently has an important role in supporting National Development. Development of Human Resources and utilization of Natural Resources and strengthening of infrastructure starts with the smallest government unit, namely the Village. Development no longer uses top down system (development from the center to the regions) but uses bottom up system (development that starts from the region), this proves that the village as a native community unit of the Indonesian people has its existence again. As a Welfare State, the Constitution of the Unitary State of the Republic of Indonesia (the 1945 Constitution) is explained that the State Economy is carried out based on populist economic principles that aim to improve shared prosperity, therefore development at every level of government, including Village governments by utilizing BUMDes for welfare village communities must be carried out based on the principles of people’s economy.